Pelatihan Musik Materi Pola Ritme pada Guru TK di TK Fkip Universitas Syiah Kuala - Samsuri Samsuri; Yuli Astuti; Ilham Septian (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
This music training with rhythm pattern material aims to improve the competence of kindergarten teachers in integrating creative and fun music learning in the early childhood education environment. The training activity was carried out at the FKIP Kindergarten, Syiah Kuala University and involved 15 teachers as participants. The training method includes initial observation, pre-test, and a series of learning stages ranging from the introduction of rhythm and tempo, rhythm composition, to joint exercises using alternative media such as used goods as musical instruments. The results of the training showed a significant increase in teachers' understanding of rhythm concepts, creativity in creating rhythm patterns, and the ability to utilize simple media as musical instruments. This training proves that with creativity and the right approach, the limitations of musical instruments are not an obstacle to organizing effective music learning in kindergarten.